Cultura narcisica e malogros na educação - Rodrigues Junior, Alvaro (1993)
The framework of the present dissertation is based on inquiries concerning certain patterns of social behavior re buked by the Brazilian society as a whole and which it considers, to a greater extent largely responsible for its material impoverishment and widespread disbelief in a better future . The complicity and inefficiency of major privileged sectors and that of the structures of justice and order dangerously reinforce this tendency in what proves to be a rampant exemption of responsibilities. Each individual acts out of the pressure originated by fear are in the benefit of his own particular interests and motivations. Under such circumstances, the category of narcissic culture paves the way to a better understanding of a variety of social matters. The features of the narcissic culture are pervasively assimilated by every stratum of the population, thus explaining~ in part, the corruption, patronage and waste, amongst other phenomena, which are typical of modern day Brazil. The aims of the present work deal with the analyses of the effects arising from the incorporation of these features by the field of institutionalized education. A particular episode involving the relationship between the National Program of Didactic Books and the educational system of the municipality of Rio de Janeiro is referencial purposes.